ALMAQASID ASSHARIA AS A BASIC DECISION MAKING ON SELECTING ISLAMIC PROPERTY - Kiki Damayanti; Atiqi Chollisni Nasution (STES Islamic Village, 2019)
This study aims to analyze the role of Almaqasid assharia as a basic decision of Muslim consumers to choose property. The research method uses rating scale as a measuring tool to know the elements of maqashid al-syariah, these are consist of protecting the religion (hifdzu-din), protecting the soul (hifdzu-nafs), protecting the mind (hifdzu-'aql), protecting offspring (hifdzu-nasl), and protecting property (hifdzu-mal. The results of this study indicate that the elements of Maqashid al-Shariah play a very important role to influence Muslim consumer’s decision, especially from the element of protecting religion (hifdzu-din), protecting the property (hifdzu-mal), and protecting the offspring (hifdzu-nasl). The study expects that the results may enrich and expand further the future research in the same field.